International Society of Sport Psychology (2008)
The International Society of Sport Psychology (ISSP) is an organization devoted to promoting research, practice, and development in the discipline of sport psychology throughout the world. The ISSP is a multidisciplinary association of scholars whose research interests focus on some aspects of sport psychology. The Society exists to (a) encourage and promote the study of human behaviour within sport, physical activity, and health settings; (b) facilitate the sharing of knowledge through a newsletter, meetings and a quadrennial congress, and (c) improve the quality of research and professional practice in sport psychology. The Society also endeavours to foster peace and understanding among people from all countries. Members of the Society include researchers, psychologists, educators, coaches and administrators, as well as students and athletes interested in sport psychology.